Penyusunan Program Parenting bagi Pengelola dan Pendidik PAUD di Nagari Lubuk Jantan Kecamatan Lintau Buo Utara - Syuraini, Syuraini; Setiawati, Setiawati; Sunarti, Vevi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2018)
Over time, advances in science and technology are increasingly high but problems are increasing, and challenges are increasing. Likewise, formal, non-formal and informal education always has a weak point on every line. This condition requires educators and educational institutions to think even harder so as not to run over with the progress of the times. Collaboration between institutions and the education environment is absolutely necessary so that there will be no regrets later and children's education can be developed optimally. One way that can be done in early childhood education is to create a mature cooperation program and this program must be well designed.Keywords: Parenting, Early Childhood Education (PAUD)